2013
DOI: 10.1186/1471-2474-14-341
|View full text |Cite
|
Sign up to set email alerts
|

Gait pattern in 9-11-year-old children with generalized joint hypermobility compared with controls; a cross-sectional study

Abstract: BackgroundTo study differences in gait patterns in 10-year-old children with Generalized Joint Hypermobility (GJH) and with no GJH (NGJH).MethodsA total of 37 children participated (19 GJH, 18 NGJH, mean age 10.2 (SD 0.5) years). Inclusion criteria for GJH were a Beighton score of ≥5, with at least one hypermobile knee joint; for NGJH a Beighton score of ≤4, and no hypermobile knees and for both groups no knee pain during the previous week. All children were recorded by five video cameras, while they walked ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
(63 reference statements)
2
16
0
Order By: Relevance
“…Shih et al [36] reported comparable mean peak knee add/abd and knee external/internal rotation values of−2.21 ± 4.42 – 3.42 ± 4.89 and−10.18 ± 6.54 – 3.08 ± 5.07 respectively. The studies by Nikolajsen et al [44] and Kung et al [45] reported only on the joint kinematics during the stance phase of children aged 10 years old and reported similar hip, knee and ankle mean peak values as see in our study for the stance phase. For example, Kung et al [45] reported mean peak knee F, ankle DF and PF of 41.74 ± 3.72; 10.18 ± 3.15 and−11.78 ± 5.14 respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Shih et al [36] reported comparable mean peak knee add/abd and knee external/internal rotation values of−2.21 ± 4.42 – 3.42 ± 4.89 and−10.18 ± 6.54 – 3.08 ± 5.07 respectively. The studies by Nikolajsen et al [44] and Kung et al [45] reported only on the joint kinematics during the stance phase of children aged 10 years old and reported similar hip, knee and ankle mean peak values as see in our study for the stance phase. For example, Kung et al [45] reported mean peak knee F, ankle DF and PF of 41.74 ± 3.72; 10.18 ± 3.15 and−11.78 ± 5.14 respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Although speed affects cadence, step length, stride length and other spatiotemporal parameters, as well as kinematics during gait, our study did not show a significant difference in walking speed between younger and older children [11, 15, 16, 43]. The median speed for the group in the current study compares well with international research based on Mexican children (6–13 years), Australian children (5–13 years) and American children (9–11 years) who walked at a self-selected speed of 1.13(±0.19) ms -1 , 1.37(±0.17) ms -1 and 1.22 (±0.04) ms -1 respectively [35, 37, 44]. Thus, 6–10-year-old South African children’s spatiotemporal parameters of gait fall within the international norms when compared with those of other countries.…”
Section: Discussionsupporting
confidence: 81%
“…There is a plethora of studies reporting that patients with BJHS suffer from chronic MSP that may affect their daily lives (Kumar & Lenert, 2017; Morris et al, 2017; Leone et al, 2009; Hakim, Malfait & Paepe, 2010; Grahame & Jenkins, 1972; Scheper et al, 2013; Chustecka, 2004; Grahame, 2000b; Simonsen et al, 2012; Nikolajsen et al, 2013; Voermans et al, 2010; Engelbert et al, 2003; Hanewinkel-Van Kleef et al, 2009). On the other hand, studies looking at a correlation of GJH and MSP have shown inconclusive results only.…”
Section: Discussionmentioning
confidence: 99%
“…The main complaint of individuals with symptomatic GJH is chronic musculoskeletal pain (MSP) that may affect their daily activities, leading to a decreased quality of life (Kumar & Lenert, 2017; Morris et al, 2017; Leone et al, 2009; Hakim, Malfait & Paepe, 2010; Scheper et al, 2013; Chustecka, 2004; Grahame, 2000b; Simonsen et al, 2012; Nikolajsen et al, 2013). Some individuals complain of pain in several joints (Grahame & Jenkins, 1972), fatigue (Voermans et al, 2010), muscle weakness (Scheper et al, 2014; Engelbert et al, 2003), or diminished motor performance (Hanewinkel-Van Kleef et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“… 33 However, different stabilization strategies (kinetic patterns) have also been shown. 31 , 32 , 34 , 35 In children 36 with nonsymptomatic GJH, only deviations in gait kinematics were observed in terms of lowered joint momentum of the lower extremity. Similar findings were also shown in adults.…”
Section: Part 1: Challengesmentioning
confidence: 99%